A feasibility study for high‐resolution silicon array detector performance in the magnetic field of a permanent magnet system. Issue 9 (12th July 2019) - Alnaghy, Sarah J.; Causer, Trent; Gargett, Maegan; Roberts, Natalia; Petasecca, Marco; Oborn, Brad M.; Rosenfeld, Anatoly B.; Holloway, Lois; Metcalfe, Peter
Abstract : Purpose: Magnetic field effects on dose distribution and detector functionality must be well understood. The detector utilized to investigate these magnetic field effects was the DUO silicon array detector; the performance of this high spatial resolution detector was assessed under these conditions. The results were compared to Gafchromic EBT3 film to highlight any intrinsic magnetic field effects in the silicon. The results were also compared to previously published MagicPlate‐512 (M512) data. The DUO has an improved spatial resolution (200 µm) over the M512 (2 mm). Methods: A permanent magnet named Magnetic Apparatus for RaDiation Oncology Studies (MARDOS) paired with a standard linear accelerator (linac) enables either transverse (1.2 T) or inline (0.95 T) orientations of the magnetic field with respect to the radiation beam. A 6 MV Varian 2100C Linac provided the radiation component for the measurements. The DUO detector has 505 sensitive volumes (each volume measuring 800 × 40 × 100 µm 3 ) organized in two orthogonal, linear arrays. The DUO was embedded in a solid water phantom in the first set‐up and then a solid lung phantom in the second set‐up and placed between the magnet cones. Beam profiles were compared under the magnetic field conditions and 0 T. Small field sizes from 0.8 × 0.8 cm 2 up to 2.3 × 2.3 cm 2 were investigated. The size of the air gap above the sensitive volumes of the DUO was investigated in the transverse orientation to assess the anticipated magnetic field effects. Full width at half maximum (FWHM), 80–20% penumbral widths and maximum dose differences between detectors and between the presence/absence of a magnetic field were investigated. Symmetry was also assessed for investigation of profile skewness under the transverse field. Results: The penumbral widths measured by the DUO detector demonstrated good agreement with film and the M512 to within an average of 0.5 mm (within uncertainty: ±1 mm). The static inline magnetic field had minimal effect on the profiles in solid water. As expected, the lower density of solid lung meant that this material was more susceptible to demonstrating magnetic field effects in the dose deposited. The greatest penumbral narrowing due to the inline field (0.7 mm) occurred in lung. Central axis dose increase was greatest in lung (maximum: 9%). The transverse field widened penumbra, most notably in the solid lung phantom, by a maximum of 2.3 mm. The largest asymmetry due to the transverse field (4.6%) was also in solid lung. When the air gap above the DUO was filled with bolus, the dose maximum measured by the DUO was within 1.4% of film. Conclusions: The DUO detector has been shown to be successful in accurately describing the dose changes for small field sizes to within a 200‐µm resolution in an environment resembling that of an MRI‐linac. The DUO measurements were in agreement with both film and the M512 measurements, and therefore the DUO was found to be an appropriate alternative to the M512, with improvement in terms of its higher spatial resolution. MARDOS provided a suitable environment for these preliminary tests before progressing to the MRI‐linac.